IMPLEMENTASI SOCIAL EMOTIONAL LEARNING (SEL) DALAM MEMBANGUN LINGKUNGAN INKLUSIF DI SEKOLAH DASAR - Resya Waryani; Yuli Kurniawati Sugiyo Pranoto; Ngabiyanto; Wadiyo; Tri Joko Raharjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The demands of modern society require children to possess strong social-emotional skills, especially in inclusive elementary school settings where students come from diverse backgrounds and have various needs. This study aims to explore the implementation of Social-Emotional Learning (SEL) as a strategy to foster an inclusive learning environment, enhance students’ emotional well-being, and improve their social interaction and academic performance. This descriptive qualitative research employed data collection techniques including observation, interviews, and documentation. The results reveal that SEL helps students including those with special needs recognize and manage their emotions, build positive relationships, and develop empathy toward differences. Strategies applied by teachers include positive reinforcement, storytelling focused on emotions, and cooperative learning. However, several challenges persist, such as limited teacher training and the lack of systematic implementation guidelines. Overall, the study affirms that SEL significantly contributes to establishing an inclusive, safe, and supportive school culture.